Answer:
(2.83 , 1 , 4)
Explanation:
![2x+2y-z=4\\4x-2y-2z=2\\3x+3y-4z=-4\\](https://img.qammunity.org/2021/formulas/mathematics/college/wl5g8ibiq7ipgmtasysmjywui36zwt63nm.png)
Rewrite these equations in matrix form
![\left[\begin{array}{ccc}2&2&-1\\4&-2&-2\\3&3&-4\end{array}\right] \left[\begin{array}{ccc}x\\y\\z\end{array}\right]=\left[\begin{array}{ccc}4\\2\\-4\end{array}\right] \\](https://img.qammunity.org/2021/formulas/mathematics/college/ivtd89tyo3b8novqvks21ejr5jwmt9ux1h.png)
we can write it like this,
![AX=B\\X=A^(-1)B](https://img.qammunity.org/2021/formulas/mathematics/college/cdi5yc1wwru1r4dy0jqin2nvdwymi2s596.png)
so to solve it we need to take the inverse of the 3 x 3 matrix A then multiply it by B.
We get the inverse of matrix A,
![A^(-1)=\left[\begin{array}{ccc}7/15&1/6&-1/5\\1/3&-1/6&0\\3/5&0&-2/5\end{array}\right] \\](https://img.qammunity.org/2021/formulas/mathematics/college/12ghnibozau683p2gtdaaihplv35x12s9v.png)
now multiply the matrix with B
![X=A^(-1)B\\\\\left[\begin{array}{ccc}x\\y\\z\end{array}\right] =\left[\begin{array}{ccc}7/15&1/6&-1/5\\1/3&-1/6&0\\3/5&0&-2/5\end{array}\right]\left[\begin{array}{ccc}4\\2\\-4\end{array}\right] \\\\\\\left[\begin{array}{ccc}x\\y\\z\end{array}\right] =\left[\begin{array}{ccc}2.83\\1\\4\end{array}\right] \\](https://img.qammunity.org/2021/formulas/mathematics/college/jn39g0v85l5l6i6772y2b1r0hwcvok4vi3.png)